Dual benefits of polyacrylamide and other soil amendments: Mitigation of soil nutrient depletion and improvement of use‐efficiency in midland agro‐ecology, Ethiopia. (5th July 2022) - Mulualem, Temesgen; Adgo, Enyew; Meshesha, Derege Tsegaye; Tsunekawa, Atsushi; Haregeweyn, Nigussie; Tsubo, Mitsuru; Kebede, Birhanu; Ebabu, Kindiye; Berihun, Mulatu Liyew; Wubet, Anteneh; Fekadu, Genetu; Demissie, Simeneh; et al.
Abstract: Polyacrylamide (PAM) mitigates soil nutrient depletion and increases nutrient utilization; however, the effect of PAM combined with other amendments have not been tested much under field condition. The objective of our study was, therefore, to identify the best combination of amendments that can improve soil nitrogen (N) and phosphorus (P) balances while maximizing utilization efficiency and profitability under teff cultivation. A field experiment was carried out for 2 years in the midland agroecology of Ethiopia. A total of 24 experimental plots were designed using RCBD with three replications. The treatments were PAM (40 kg ha −1 ), biochar (B = 8 t ha −1 ), lime (L = 4 t ha −1 ), gypsum (G = 5 t ha −1 ), PAM+B, PAM+L, PAM+G, and a control. N and P inflows from atmospheric deposition, biological fixation, and fertilizers; and outflows by water erosion, leaching, gaseous emissions, and harvested products were monitored in all plots via NUTrient MONitoring approach. Results showed that all the applied soil amendments improved nutrient balances (8–134%) compared with the control. Of the measured outflows, harvested products (43–60%) and water erosion (14–31%) were the major contributors to N depletion, followed by leaching (15–23%) and gaseous emissions (11–13%). Among the soil amendments, PAM+L appreciably reduced P loss from water erosion (61%); and N losses from erosion, leaching, and emissions by 55, 10, and 3%, respectively; and increased N use efficiency by 31% compared with the control. Moreover, PAM+L provided a net benefit much higher compared with others. Thus, application of PAM+L would be an effective strategy for sustainable agriculture, especially in acidic and degraded dryland areas.